Mulheres em trabalho de telemarketing em home office: impactos do trabalho-família - Moraes, Mariana Futema (Universidade Federal de São Carlos, 2023)
This article addresses home office work adopted by telemarketing companies due to the Covid-19 pandemic, which appears to be a continuing trend in the current market in the world. This problem consists of one question: What are the impacts on companies and employees of adopting telemarketing from home during the Covid-19 pandemic? The central objective of the research is to analyze the impacts caused by changes in the routine of telemarketing employees. The specific objectives are to address the history of working from home, identifying the benefits that are based on internal and external factors, such as the relationship between women and the balance between professional and personal life, the employee's quality of life and cost reduction for the company. The results showed that employees, still following the precautions and recommendations, face precarious work conditions, such as: extended working hours, job insecurity and the merger of the work and home environment without adequate preparation.
Women in telemarketing working from home: work-family impacts
Keywords: Telemarketing Home Office; Covid-19; Qualidade de Vida; Quality of Life; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO DE RECURSOS HUMANOS